2021
DOI: 10.1503/cmaj.210132
|View full text |Cite
|
Sign up to set email alerts
|

The mobility gap: estimating mobility thresholds required to control SARS-CoV-2 in Canada

Abstract: BACKGROUND: Nonpharmaceutical interventions remain the primary means of controlling severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) until vaccination coverage is sufficient to achieve herd immunity. We used anonymized smartphone mobility measures to quantify the mobility level needed to control SARS-CoV-2 (i.e., mobility threshold), and the diference relative to the observed mobility level (i.e., mobility gap). METHODS:We conducted a time-series study of the weekly incidence of SARS-CoV-2 in Canad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 24 publications
0
22
1
Order By: Relevance
“…Mobility and personal contact were not nearly as reduced by government mandates in the second and third waves. 4 Mask mandates were introduced in July 2020 and most of the public was willing to wear masks indoors thereafter.…”
Section: Provincial and Territorial Responsesmentioning
confidence: 99%
“…Mobility and personal contact were not nearly as reduced by government mandates in the second and third waves. 4 Mask mandates were introduced in July 2020 and most of the public was willing to wear masks indoors thereafter.…”
Section: Provincial and Territorial Responsesmentioning
confidence: 99%
“…While highly effective vaccines are readily available in the United States, uptake remains low [1] and interventions aimed at minimizing human contact remain necessary to mitigate the spread of 1 INTRODUCTION SARS-CoV-2 [2,3,4,5]. Decreasing mobility patterns within populations, has been shown to be an effective strategy to curb infectious disease transmission.…”
Section: Introductionmentioning
confidence: 99%
“…A modelling study from China showed 20-60% reductions in mobility notably controlled the spread of SARS-CoV-2 [16]. A study from Canada showed that reductions in mobility strongly predict future control of SARS-CoV-2 growth rates [5]. However, in the absence of social distancing interventions, the link between changes in population-level mobility and COVID-19 remains unclear [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…While highly effective vaccines are readily available in the United States, uptake remains low [1] and interventions aimed at minimizing human contact remain necessary to mitigate the spread of SARS-CoV-2 [2,3,4,5]. Decreasing mobility patterns within populations, has been shown to be an effective strategy to curb infectious disease transmission.…”
Section: Introductionmentioning
confidence: 99%
“…A modelling study 2 METHODS from China showed 20-60% reductions in mobility notably controlled the spread of SARS-CoV-2 [16]. A study from Canada showed that reductions in mobility strongly predict future control of SARS-CoV-2 growth rates [5]. However, in the absence of social distancing interventions, the link between changes in population-level mobility and COVID-19 remains unclear [8,9].…”
Section: Introductionmentioning
confidence: 99%